2016
DOI: 10.1007/s00114-016-1387-7
|View full text |Cite
|
Sign up to set email alerts
|

Generation of functional hepatocyte-like cells from human deciduous periodontal ligament stem cells

Abstract: Human deciduous periodontal ligament stem cells have been introduced for as an easily accessible source of stem cells from dental origin. Although recent studies have revealed the ability of these stem cells in multipotential attribute, their efficiency of hepatic lineage differentiation has not been addressed so far. The aim of this study is to investigate hepatic lineage fate competence of periodontal ligament stem cells through direct media induction. Differentiation of periodontal ligament stem cells into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Interestingly, studies conducted on the interest and attitude towards the use of stem cells in regenerative therapy received a highly positive response from the dentists in South Africa (73%) and nursing students in USM (76.1%) 26,27 . As, several in vitro and in vivo studies have shown the regenerative potential of SHED/DPSCs (to cure or improve the condition of diseases, such as type 1 diabetes, neurological diseases, immunodeficiency diseases, and diseases of bone and cartilages) 10,[13][14][15][16]28 , researchers should take the initiatives to explore the potential of SHED/DPSCs. Dentists or physicians are needed to explain the potential of SHED/DPSCs to the patients to make them aware of their presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies conducted on the interest and attitude towards the use of stem cells in regenerative therapy received a highly positive response from the dentists in South Africa (73%) and nursing students in USM (76.1%) 26,27 . As, several in vitro and in vivo studies have shown the regenerative potential of SHED/DPSCs (to cure or improve the condition of diseases, such as type 1 diabetes, neurological diseases, immunodeficiency diseases, and diseases of bone and cartilages) 10,[13][14][15][16]28 , researchers should take the initiatives to explore the potential of SHED/DPSCs. Dentists or physicians are needed to explain the potential of SHED/DPSCs to the patients to make them aware of their presence.…”
Section: Discussionmentioning
confidence: 99%
“…DPSCs have drawn considerable attention just after their discovery by Gronthos et al in the year 2000 12 , and several researches have been reported their potential to differentiate into different types of cell lineages such as cardiomyocytes, beta cells, hepatocytes, neuronal cells etc. 10,[13][14][15][16] . Their MSCs like characteristics and immunomodulatory properties have also been acknowledged by several researchers 11,17 .…”
Section: Introductionmentioning
confidence: 99%
“…PDLSCs have similar features to BMMSCs and exhibit self-renewal capacity and multipotency[ 39 ]. These cells have the potential to undergo triploblastic differentiation with the ability to differentiate into not only osteoblasts, adipocytes, chondrocytes, cementoblasts, and tendon/ligament fibroblasts[ 40 , 41 ] but also myocytes[ 42 ], neural cells[ 43 ], retinal cells[ 44 ], endothelial cells[ 45 ], pancreatic islet cells[ 46 ], and hepatic cells[ 47 ]. In addition, PDLSCs express cell surface markers such as STRO-1, CD146/MUC18[ 36 ], CD44, and CD90 (markers associated with stromal cells), CD105 and CD166 (markers associated with stromal cells and endothelial cells)[ 48 ], and CD10, CD26, CD29, CD73, and CD349/FZD9[ 49 ] but do not express hematopoietic cell surface markers such as CD31 and CD45, similar to BMMSCs[ 50 ].…”
Section: What Are Pdlscs?mentioning
confidence: 99%